KULTURMUNDIGKEIT UND INTERKULTURELLE KOMPETENZ LITERATURE IN CONTEMPORY FOREIGN LANGUAGE TEACHING - jaiser, gerhard (LITERA, 2015)
<img src="data:image/png;base64,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